The Individual’s Aptitude For Career Advancement - Ala' Odeh; Majdi Anwar Quttainah (Journal of International Conference Proceedings (JICP), 2018)
This paper investigates the correlation between nationality and the individual’s aptitude and willingness for career advancement. It is assumed that: Kuwait’s business demographic is generally composed of nationals and foreigners, foreign residents make up the majority portion of the work force in the private work sector whereas national residents makeup the majority in public work sectors,the turn - over rate in public sector is lower than that’s of the private sector, foreign residents are more likely to advance their career in the private sector than that of the public, it is also assumed that there are career advancement opportunities for foreign residents in Kuwait's private business sector. The high turn-over rate in Kuwait's private business sector may indicates the lack of economic stability, lack of poignant stability, lack of organization loyalty, lack of strong organization culture, or lack of leadership and effective & efficient management. Based on the previously discussed assumptions, Weather or not the foreign residential of the Kuwaiti demographic are more likely to be “scanners” in career advancement manifested a debatable hypothesis. Finally, thisresearch will prove the correlation between nationality and the dedication to career growth to identify weather foreign residents in Kuwait are more likely to be “scanners” in the term referenced to advancement behavioral categories index1.